Pembelajaran Teater Modern Menggunakan Metode Drill Di Sekolah Menegah Atas Islam Az – Zahrah Palembang - Nur Anisa Putri; Nugroho Notosutanto Arhon Dhony; Auzy Madona Adoma (Mahesa Research Center, 2022)
Modern theater learning is one of the cultural arts learning materials at Islamic Senior High School Az – Zahrah Palembang. The drilling method is a way of teaching by doing training activities continuously to gain dexterity and skills. This study aims to describe the learning process of modern theater using the drill method in class XI at SMA Islam Az – Zahrah Palembang. The research method used is a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study on teachers and 33 students of class XI, showed that modern theater learning using the drill method went well.